1998
DOI: 10.1007/s002800050739
|View full text |Cite
|
Sign up to set email alerts
|

Metabolism and ribonucleotide reductase inhibition of ( E   )-2′-deoxy-2′-(fluoromethylene)cytidine, MDL 101,731, in human cervical carcinoma HeLa S 3 cells

Abstract: This study suggests that the prolonged ribonucleotide reductase inhibition by rapidly activated metabolites of MDL 101,731 in part contributes to the potent antitumor activity of this drug against various xenografts.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

1999
1999
2005
2005

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 14 publications
0
17
0
Order By: Relevance
“…In human tumors xenografted to animals it inhibits growth, and triggers apoptotic cell death of mammary, prostate, cervical and colorectal cancers, and gliomas (1,2,14,18,20,21,23).…”
mentioning
confidence: 99%
“…In human tumors xenografted to animals it inhibits growth, and triggers apoptotic cell death of mammary, prostate, cervical and colorectal cancers, and gliomas (1,2,14,18,20,21,23).…”
mentioning
confidence: 99%
“…Tezacitabine is also relatively resistant to metabolic deactivation from cytidine deaminase in other (cervical cancer) cell lines. 81 Four Phase I trials involving 70 patients with refractory solid tumours (including seven with pancreatic cancer) have shown objective antitumour activity in eight out of 70 patients (one partial response and seven with stable disease). 82 The recommended schedule for Phase II studies is one treatment every 2 weeks, at a minimum dose of 270 mg/m 2 .…”
Section: Cytosine Analoguesmentioning
confidence: 99%
“…7 Second, tezacitabine is approximately 30-fold more resistant than gemcitabine to metabolic inactivation through deamination by cytidine deaminase. 8 The latter could provide an advantage for tezacitabine in the treatment of cancer types in which cytidine deaminase levels are elevated or in individual patients who have tumors with high levels of the enzyme. For example, studies with human tumor xenografts suggest that many gastrointestinal tumors have high cytidine deaminase levels (unpublished data), and thus tezacitabine may be particularly useful in the treatment of this group of malignancies.…”
mentioning
confidence: 99%
“…These agents are potentially complementary because tezacitabine has been shown in in vitro studies to cause an accumulation of tumor cells in the S-phase of the cell cycle 6,9,10 and 5-FU has activity that is somewhat S-phase dependent. Combinations of tezacitabine with 5-FU and other S-phasespecific drugs have shown synergistic antiproliferative activity in vitro, 8 and studies with human and murine xenografts have shown synergistic and additive antitumor effects in vivo.…”
mentioning
confidence: 99%